(untitled) (Brazilian Journal of Health Research, 2023)
Introduction: Despite the positive results in the scientific studies of the Kangaroo, there are difficulties in its implementation and dissemination in the health system, such as the lack of resources (human and financial) and differences in theoretical and practical knowledge. Objectives: To identify differences as theoretical and practical methods on methods that can be used among professionals working in Neonatal Units of public and philanthropic hospitals in the state of Espírito Santo, as well as the profile of health professionals working in these services. Methods: Evaluation study with a survey research character, with a qualitative approach, approved under CAAE 42652621.5.0000.5060. Data collection was carried out by an electronic periodical (Google Forms), containing open and closed questions, from May to October 2020, 28 participants from four institutions participating in the research. The recorded data were analyzed using descriptive statistics. For qualitative data, an approach to content analysis was performed. Results: All female professionals were observed, most of them aged between 31-40 years. A hospital has most professional categories. It was found that professionals have difficulties in understanding and implementing the method presented in its entirety. The reasons were cited as several barriers and facilitators for the team’s adherence and implementation of the method. Numerous benefits were listed by professionals. Conclusions: Education becomes necessary that the difficulties for the implementation and adherence to the Kangaroo method are in depth and the education practices intensified, associated with investments in humanization, continued and infrastructure.